Implementation Of AES Algorithm For Text Message Encryption And Decryption Process - Sukiman, T. Sukma Achriadi; Sandy, Cut Lika Mestika; Meiyanti, Rini; Rizal, Reyhan Achmad; Anshari, Said Fadlan (Gameology and Multimedia Expert, 2026)
In the development of secure digital communication, the Advanced Encryption Standard (AES) algorithm particularly the AES-128 variant plays a crucial role in maintaining the confidentiality and integrity of textual data transmitted over public networks. This study aims to design, implement, and analyze a web application prototype for the encryption and decryption process using the AES-128 algorithm based on the PyCryptodome library in the Python programming language, executed through the Flask framework. The developed system offers a simple user interface that allows users to input encryption keys and text, and obtain results in real time. Strict input length validation is applied to ensure that the cryptographic process runs optimally. Testing results show that AES-128 can be efficiently implemented in a lightweight web server environment, with fast processing time and high accuracy. Although the system uses ECB mode, which has known security weaknesses, the prototype is effective for small-scale text communication needs. This study also recommends further development using CBC mode and authentication features to enhance security.